2022
DOI: 10.3233/prm-200799
|View full text |Cite
|
Sign up to set email alerts
|

Decreased access to therapeutic services for children with disabilities during COVID-19 stay-at-home orders in Western Pennsylvania

Abstract: PURPOSE: Assess the effects of stay-at-home orders on access to services utilized by families of children with disabilities (CWD). METHODS: Cross-sectional weekly surveys were fielded over four weeks, during which western Pennsylvania was under stay-at-home orders. Respondents were divided into families of CWD (N = 233) or without CWD (N = 1582). Survey questions included measures of socio-economic status, and families of CWD answered questions regarding access to services pre and post-initiation of stay-at-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…More than 8 in 10 caregivers also reported interruptions in their child's progress toward IEP or 504 plan goals. These findings are consistent with literature earlier in the pandemic where caregivers reported disruptions in school-based services and subsequent declines in their child's functioning due to the COVID-19 pandemic ( 13 17 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than 8 in 10 caregivers also reported interruptions in their child's progress toward IEP or 504 plan goals. These findings are consistent with literature earlier in the pandemic where caregivers reported disruptions in school-based services and subsequent declines in their child's functioning due to the COVID-19 pandemic ( 13 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies surveying caregivers of children with IDD assessed changes in access to educational and therapeutic services due to the COVID-19 pandemic. A Family Strengths Survey disseminated in Western Pennsylvania indicated that 76% of families of children with disabilities had reduced access to early intervention services and 81% had reduced access to school-based therapies due to COVID-19 school closures ( 13 ). In a different survey examining special education services, 60% of caregivers reported that following school closures, their children received fewer special education hours and a significant decrease in the number of related service hours compared to what they were supposed to receive, as indicated by their individualized education program ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The adjusted odds of neonatologist referral was more than three times higher during COVID- While the restrictive nature of SAH measures and resultant social isolation may have exacerbated developmental considerations for preterm infants, environmental stressors likely placed an additional burden on these families. Survey studies on caregivers of children with disabilities have echoed such concerns, reporting uncertainty regarding the long-term impact of COVID-19 on their children's development and feeling overwhelmed with the disruption of essential services and therapies (10,11,13). They additionally reported higher levels of stress, more job and income loss, decreased wellbeing and more sadness or anxiety experienced during COVID-19 -all factors that affect the stability of the home environment and potentially worsen developmental outcomes (10,11,13,21,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Survey studies on caregivers of children with disabilities have echoed such concerns, reporting uncertainty regarding the long-term impact of COVID-19 on their children's development and feeling overwhelmed with the disruption of essential services and therapies (10,11,13). They additionally reported higher levels of stress, more job and income loss, decreased wellbeing and more sadness or anxiety experienced during COVID-19 -all factors that affect the stability of the home environment and potentially worsen developmental outcomes (10,11,13,21,22,23). Therefore, we are not able to disentangle the effect of teletherapy from increased neurodevelopmental need due to environmental stressors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation